2021
DOI: 10.1101/2021.08.11.455946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grandparent inference from genetic data: The potential for parentage-based tagging programs to identify offspring of hatchery strays

Abstract: Fisheries managers routinely use hatcheries to increase angling opportunity. Many hatcheries operate as segregated programs where hatchery-origin fish are not intended to spawn with natural-origin conspecifics in order to prevent potential negative effects on the natural-origin population. Currently available techniques to monitor the frequency with which hatchery-origin strays successfully spawn in the wild rely on either genetic differentiation between the hatchery- and natural-origin fish or extensive sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…One particularly informative relationship for fisheries management is that of grandparent–grandchild (Letcher and King 2001; Christie et al 2011; Sard et al 2016). Grandparent assignment with only two grandparents (e.g., two individuals in the hatchery broodstock) would allow managers to positively identify the offspring of unsampled hatchery strays and natural fish (Delomas and Campbell 2022). One major hurdle in implementing this analysis is the time span between the collection of candidate grandparents and the collection of grandchildren.…”
Section: Discussionmentioning
confidence: 99%
“…One particularly informative relationship for fisheries management is that of grandparent–grandchild (Letcher and King 2001; Christie et al 2011; Sard et al 2016). Grandparent assignment with only two grandparents (e.g., two individuals in the hatchery broodstock) would allow managers to positively identify the offspring of unsampled hatchery strays and natural fish (Delomas and Campbell 2022). One major hurdle in implementing this analysis is the time span between the collection of candidate grandparents and the collection of grandchildren.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of our microsatellite marker panel revealed that as few as seven microsatellite markers could confidently identify full-sibling individuals (Figure 2), implying that a smaller marker panel may have been sufficient to infer parentage. A reduction in marker panel size could decrease costs associated with genotyping; however, smaller marker panels may suffer from elevated false positive and false negative rates when used for parentage analysis (Delomas and Campbell 2022). In our study, false positive and false negative rates were 0% and 2.7%, respectively, and were in line with estimates from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Once libraries were sequenced, data were run through in‐house quality control pipelines to ensure that there was no contamination, sample failure, or duplication and a random number of samples were rerun to ensure genotype calls match (Delomas et al. 2019). Genotypes of the 9,830 broodstock baseline and adult returns used in this analysis can be found at http://fishgen.net, data set ID #20210320.…”
Section: Methodsmentioning
confidence: 99%